Inorganic functional slurry, front silver-aluminum slurry of N-type TOPCon solar cell and preparation method thereof
By introducing inorganic functional additives into the front silver aluminum paste of N-type TOPCon solar cells, reacting with silicon substrates to form compound or alloy structures, the problems of contact resistance and line resistance are solved, and the photoelectric conversion efficiency and slurry dispersion are improved. sex.
Patent Information
- Application Number
- CN202310569991.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-05-19
AI Technical Summary
The front silver aluminum paste of the existing N-type TOPCon solar cells has room for improvement in contact resistance and line resistance, affecting the photoelectric conversion efficiency.
Using an inorganic functional slurry, including 55 to 85 parts by mass of an organic carrier, 2 to 20 parts by mass of an inorganic functional additive, and 2 to 10 parts by mass of a dispersant, the mixture is formed by mixing it with conductive silver powder, aluminum powder and glass powder. The slurry reacts with the silicon substrate during sintering to form a compound or alloy structure, reducing contact resistance and line resistance.
It effectively reduces the contact resistance and line resistance of the battery cell, improves the photoelectric conversion efficiency, and improves the dispersion and sintering performance of the slurry.
Smart Images

Figure CN116598042B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive paste for solar cells, and in particular relates to an inorganic functional paste, a front silver-aluminum paste for an N-type TOPCon solar cell, and a preparation method thereof. Background Art
[0002] TOPCon (tunneling oxide passivation contact) cells are a type of photovoltaic crystalline silicon cells with advantages such as high photoelectric conversion efficiency, low attenuation performance, and high mass production cost performance. The Topcon cell structure is an N-type silicon substrate cell. An ultra-thin layer of silicon oxide is prepared on the back of the cell, and then a thin layer of doped silicon is deposited. The two together form a passivation contact structure, which effectively reduces surface recombination and metal contact recombination. The front of the N-type TOPCon cell is different from the front of the conventional N-type cell. Conventional N-type cells are generally passivated with a homogeneous film of SiNx:SiO2, and the passivation effect is limited; while the TOPCon cell is mainly passivated with a heterogeneous film stack of SiNx:Al2O3. The passivation effect and anti-reflection performance of this structure are better than homogeneous film passivation.
[0003] Although TOPCon cells have the advantage of eliminating back-field surface recombination and effectively reducing losses, with the deepening of understanding of slurries and the increasing requirements for improving cell efficiency, innovation is still needed on the existing basis to further reduce contact resistance and / or line resistance and improve photoelectric conversion efficiency. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art, and provides an inorganic functional slurry, a front silver-aluminum slurry for an N-type TOPCon solar cell, and a preparation method thereof.
[0005] In one aspect of the present invention, an inorganic functional paste is provided, which is used for the front silver-aluminum paste of an N-type TOPCon solar cell, and the inorganic functional paste comprises:
[0006] 55 to 85 parts by weight of an organic carrier;
[0007] 2 to 20 parts by weight of inorganic functional additives;
[0008] 2 to 10 parts by mass of a dispersant;
[0009] 10 to 30 parts by mass of solvent.
[0010] Optionally, the inorganic functional additive includes at least one of zinc oxide, lead oxide, titanium oxide, antimony trioxide, tellurium oxide, aluminum-magnesium alloy, silver oxide, and silver-bismuth alloy.
[0011] Optionally, the D50 particle size of the inorganic functional additive is 0.08 um to 1.6 um.
[0012] Optionally, the dispersant includes a first dispersing component and a second dispersing component; wherein,
[0013] The first dispersed component is an organic substance containing -OH and -COOH;
[0014] The second dispersing component is acetylenic alcohol-modified silicone.
[0015] Optionally, the content of the first dispersed component is 1 to 5 parts by mass, and the content of the second dispersed component is 1 to 5 parts by mass.
[0016] Optionally, the first dispersing component includes at least one of alcohol benzoate, ethyl glycolate, fatty acids, and phosphonates.
[0017] Optionally, the organic vehicle comprises 3 to 15 parts by mass of acrylic resin.
[0018] Another aspect of the present invention provides a front silver-aluminum paste for an N-type TOPCon solar cell, the front silver-aluminum paste comprising:
[0019] 75-87 parts by mass of conductive silver powder;
[0020] 1 to 5 parts by mass of aluminum powder;
[0021] 3 to 15 parts by weight of an organic carrier;
[0022] 2 to 6 parts by weight of glass powder;
[0023] 1 to 3.5 parts by weight of an auxiliary agent;
[0024] 1 to 4 parts by weight of an inorganic functional slurry, wherein the inorganic functional slurry is the inorganic functional slurry described above.
[0025] Another aspect of the present invention provides a method for preparing the front silver-aluminum paste of the N-type TOPCon solar cell described above, the method comprising:
[0026] forming an inorganic functional slurry;
[0027] Conductive silver powder, aluminum powder, glass powder, organic carrier, additive and the inorganic functional slurry are uniformly mixed and ground to obtain an N-type TOPCon solar cell.
[0028] Optionally, the forming of the inorganic functional slurry comprises:
[0029] Adding the inorganic functional additive to the first dispersed component and stirring evenly to obtain a first dispersed slurry;
[0030] Adding the second dispersed component into the first dispersed slurry and stirring evenly to obtain a second dispersed slurry, and performing a stirring and dispersing treatment;
[0031] The treated second dispersed slurry is uniformly mixed with an organic carrier and a solvent to obtain an inorganic functional slurry.
[0032] The present invention provides an inorganic functional slurry, a front silver-aluminum slurry for an N-type TOPCon solar cell, and a preparation method thereof. The inorganic functional slurry comprises: 55 to 85 parts by mass of an organic carrier; 2 to 20 parts by mass of an inorganic functional additive; 2 to 10 parts by mass of a dispersant; and 10 to 30 parts by mass of a solvent. When the inorganic functional slurry of the present invention is used for the front silver-aluminum slurry of an N-type TOPCon solar cell, the inorganic functional additive can promote the sintering of the silver layer, make the silver and silicon conductive, so that the cell line resistance and / or contact resistance are reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a flowchart of a method for preparing a front silver-aluminum paste according to an embodiment of the present invention;
[0034] Figure 2 This is a comparison diagram of the morphologies of antimony trioxide and silicon after the reaction of Examples 10 and 11 of the present invention;
[0035] Figure 3 The morphology of the front silver-aluminum paste after the reaction with silicon in Examples 10 and 11 of the present invention;
[0036] Figure 4 The morphology of the front silver-aluminum paste after the reaction with silicon in Examples 12 and 13 of the present invention;
[0037] Figure 5 This is the morphology of the front silver-aluminum paste after the reaction with silicon in Examples 14 and 15 of the present invention. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0039] Unless otherwise specified, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The terms "including" and the like used in the present invention neither limit the mentioned numbers, steps, operations and / or their groups, nor exclude the presence or addition of one or more other different numbers, steps, operations and / or their groups.
[0040] In one aspect of the present invention, an inorganic functional slurry is provided for the front silver-aluminum slurry of an N-type TOPCon solar cell. The inorganic functional slurry comprises: 55 to 85 parts by mass of an organic carrier; 2 to 20 parts by mass of an inorganic functional additive; 2 to 10 parts by mass of a dispersant; and 10 to 30 parts by mass of a solvent.
[0041] In this embodiment, when the inorganic functional paste is used for the front silver-aluminum paste of the N-type TOPCon solar cell, it can react with the silicon substrate to form a compound or alloy structure to reduce the line resistance and / or contact resistance. In addition, it can also promote the sintering of the silver layer to make the silver and silicon conductive.
[0042] Specifically, in this embodiment, the inorganic functional additives include at least one of zinc oxide, lead oxide, titanium oxide, antimony trioxide, tellurium oxide, aluminum-magnesium alloy, silver oxide, and silver-bismuth alloy. During the slurry sintering process, the above-mentioned additives can not only react with silver, but also reach the silicon surface and directly react with silicon to produce a pinning structure, thereby reducing contact resistance and / or line resistance.
[0043] Furthermore, in the present embodiment, the D50 particle size of the inorganic functional additive is preferably 0.08 μm to 1.6 μm. When the inorganic functional additive is within the above preferred particle size and preferred range, the requirements of screen fine line printing can be met.
[0044] Furthermore, the dispersant includes a first dispersing component and a second dispersing component; wherein the first dispersing component is an organic substance containing -OH and -COOH; and the second dispersing component is an acetylenic alcohol-modified silicone. The content of the first dispersing component is 1 to 5 parts by mass, and the content of the second dispersing component is 1 to 5 parts by mass. In other words, the dispersant includes 1 to 5 parts by mass of the first dispersing component and 1 to 5 parts by mass of the second dispersing component.
[0045] It should be noted that, in this embodiment, the first dispersing component includes at least one of alcohol benzoate, ethyl glycolate, fatty acids, and phosphonates, wherein the fatty acids may be hydroxy-modified fatty acids or hydroxy-modified fatty acid esters.
[0046] In this embodiment, the first dispersed component can coat the inorganic functional additive powder, reduce powder agglomeration, and improve the dispersion uniformity of the additive powder. At the same time, the first dispersed component is also compatible with the organic carrier, which is conducive to improving the dispersion uniformity and dispersion stability of the inorganic functional additive powder in the slurry. The second dispersed component has a smaller surface tension, which is conducive to further improving the dispersibility of the inorganic functional additive powder coated by the dispersed component A.
[0047] Furthermore, the organic carrier includes 3 to 15 parts by weight of acrylic resin, wherein the molecular weight of the resin is 30,000-60,000, the decomposition temperature is 200-400° C., the decomposition peak is 260° C., and the decomposition residue is 0.5 parts by weight.
[0048] In this embodiment, the resin molecular weight of the organic carrier is relatively large, and the macromolecules are easy to aggregate into a film after the solvent evaporates, thereby improving printability; secondly, the organic carrier has a layered structure rather than being concentrated in a small temperature range. As the temperature rises, it evaporates in a gradient with little residue, thereby avoiding concentrated volatilization that causes pores and cracks in the electrode grid lines; furthermore, the slurry formed based on the organic carrier has good storage stability; and the dispersibility of the inorganic functional additive powder therein can also be improved.
[0049] Furthermore, the solvent includes at least one of ethanol, diethylene glycol butyl ether, diethylene glycol diethyl ether, ethylene glycol phenyl ether, dibutyl phthalate, and diethylene glycol butyl ether acetate, and the above solvents have good solubility for components such as resins.
[0050] In another aspect of the present invention, a front silver-aluminum paste for an N-type TOPCon solar cell is provided, comprising: 75 to 87 parts by mass of conductive silver powder; 1 to 5 parts by mass of aluminum powder; 3 to 15 parts by mass of an organic carrier; 2 to 6 parts by mass of glass powder; 1 to 3.5 parts by mass of an auxiliary agent; and 1 to 4 parts by mass of the inorganic functional paste described above.
[0051] In this embodiment, by introducing inorganic functional additives into the silver-aluminum paste, it can react with silicon to generate a compound or alloy structure, and the silver-aluminum alloy forms a pinning structure on the silicon surface, thereby reducing the cell line resistance and / or contact resistance on the original basis. In addition, it can also promote the sintering of conductive silver powder.
[0052] It should be noted that the organic carrier may be the same as the organic carrier described above, or may include other resins, which are not specifically limited. Its main function is to give the slurry appropriate viscosity and rheological properties and make it suitable for printing.
[0053] It should be further explained that the physical and chemical properties of inorganic phases such as aluminum powder, silver powder, glass powder, additives, etc. in the slurry are the most important factors that determine the slurry sintering behavior and ohmic contact performance. Therefore, in this embodiment, the additive is selected from at least one of zinc oxide, lead oxide, titanium oxide, antimony trioxide, tellurium oxide, aluminum-magnesium alloy, silver oxide, and silver-bismuth alloy, which can play a role in reducing the contact resistance and / or line resistance of the battery cell. In addition, the glass powder can use Pb-Zn-B-Si-In system as an inorganic bonding phase, which can fully wet the conductive silver powder and the silicon substrate, so that the conductive silver powder and the silicon substrate maintain good adhesion.
[0054] It should be noted that when the content of the auxiliary agent in this embodiment is within the above preferred range, it is beneficial to improve the uniformity and stability of the slurry and to improve the printing performance. In addition, the auxiliary agent includes but is not limited to 0.5-3 parts by mass of a defoamer and 1-5 parts by mass of a thixotropic agent, wherein the defoamer can be one or more of polydimethylsiloxane, silane copolymer, lauric acid, palmitic acid, and fatty acid glyceride; the thixotropic agent can be one or more of acrylate, polyurethane, epoxy resin, and silicone, which helps to improve functionality.
[0055] Furthermore, in order to illustrate the performance of the front silver aluminum paste, it is necessary to print it into a cell and test the IV characteristics of the cell to illustrate the contact resistance, line resistance and photoelectric conversion efficiency of the cell, and further evaluate the impact of different inorganic functional additives on the performance of the cell. Combined with Table 3, it can be seen that compared with the paste without adding inorganic functional additive powder, the line resistance and / or contact resistance of the paste with different inorganic functional additive powders are reduced to varying degrees, and the photoelectric conversion efficiency of the cell is improved.
[0056] like Figure 1 As shown, another aspect of the present invention provides a method S100 for preparing the front silver-aluminum paste of the N-type TOPCon solar cell described above, comprising steps S110 to S120:
[0057] S110, forming an inorganic functional slurry, specifically including the following process:
[0058] S1101, adding 2 to 20 parts by mass of an inorganic functional additive to 1 to 5 parts by mass of a first dispersed component and stirring the mixture to obtain a first dispersed slurry;
[0059] S1102, adding 1 to 5 parts by weight of the second dispersed component into the first dispersed slurry and stirring evenly to obtain a second dispersed slurry, and performing a stirring and dispersion treatment for 60 to 90 minutes using a dispersing paddle;
[0060] S1103, uniformly mixing the treated second dispersed slurry with 55-85 parts by mass of an organic vehicle and 10-30 parts by mass of a solvent (for example, by mixing by one or more of ultrasound, ball milling, and homogenization) to obtain an inorganic functional slurry.
[0061] S120, 75-87 parts by mass of conductive silver powder, 1-5 parts by mass of aluminum powder, 2-6 parts by mass of glass powder, 3-15 parts by mass of organic carrier, 1-3.5 parts by mass of auxiliary agent and 1-4 parts by mass of inorganic functional slurry obtained in step S110 are mixed evenly, and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0062] The preparation method of the present invention is simple, and the inorganic additive slurry and the battery slurry are formed step by step, which effectively improves the dispersibility of the slurry, and then improves the effect of the inorganic functional additive; secondly, the inorganic functional additive and the dispersant are mixed step by step during the formation of the inorganic functional slurry, and then the uniformly dispersed inorganic functional additive is mixed with the organic carrier and the solvent, so that the additive has good dispersibility in the organic carrier and the solvent, which is conducive to its application in the front silver aluminum slurry.
[0063] The following will further illustrate the preparation method of the inorganic functional paste and the front silver-aluminum paste of the N-type TOPCon solar cell in combination with several specific examples:
[0064] Example 1
[0065] This example takes the formation process of inorganic functional slurry as an example to illustrate, and the components and contents are shown in Table 1, including the following steps:
[0066] S1, adding 4.5 parts by mass of zinc oxide to 2 parts by mass of alcohol benzoate and stirring evenly to obtain a first dispersed slurry;
[0067] S2, adding 1.5 parts by mass of acetylene alcohol-modified silicone into the first dispersed slurry and stirring evenly to obtain a second dispersed slurry, and stirring and dispersing the slurry with a dispersing paddle for 60-90 minutes;
[0068] S3. Evenly mix the treated second dispersed slurry with 64 parts by mass of an organic carrier and 28 parts by mass of ethanol to obtain an inorganic functional slurry.
[0069] Example 2
[0070] This example takes the formation process of inorganic functional slurry as an example to illustrate, and the components and contents are shown in Table 1, including the following steps:
[0071] S1, adding 4.5 parts by mass of titanium oxide to 2 parts by mass of alcohol benzoate and stirring evenly to obtain a first dispersed slurry;
[0072] S2, adding 1.5 parts by mass of acetylene alcohol-modified silicone into the first dispersed slurry and stirring evenly to obtain a second dispersed slurry, and stirring and dispersing the slurry with a dispersing paddle for 60-90 minutes;
[0073] S3. Evenly mix the treated second dispersed slurry with 64 parts by mass of an organic carrier and 28 parts by mass of ethanol to obtain an inorganic functional slurry.
[0074] Example 3
[0075] This example takes the formation process of inorganic functional slurry as an example to illustrate, and the components and contents are shown in Table 1, including the following steps:
[0076] S1, adding 4.5 parts by mass of antimony trioxide to 2 parts by mass of alcohol benzoate and stirring evenly to obtain a first dispersed slurry;
[0077] S2, adding 1.5 parts by mass of acetylene alcohol-modified silicone into the first dispersed slurry and stirring evenly to obtain a second dispersed slurry, and stirring and dispersing the slurry with a dispersing paddle for 60-90 minutes;
[0078] S3. Evenly mix the treated second dispersed slurry with 64 parts by mass of an organic carrier and 28 parts by mass of ethanol to obtain an inorganic functional slurry.
[0079] Example 4
[0080] This example takes the formation process of inorganic functional slurry as an example to illustrate, and the components and contents are shown in Table 1, including the following steps:
[0081] S1, adding 4.5 parts by mass of aluminum-magnesium alloy to 2 parts by mass of alcohol benzoate and stirring evenly to obtain a first dispersed slurry;
[0082] S2, adding 1.5 parts by mass of acetylene alcohol-modified silicone into the first dispersed slurry and stirring evenly to obtain a second dispersed slurry, and stirring and dispersing the slurry with a dispersing paddle for 60-90 minutes;
[0083] S3. Evenly mix the treated second dispersed slurry with 64 parts by mass of an organic carrier and 28 parts by mass of ethanol to obtain an inorganic functional slurry.
[0084] Example 5
[0085] This example takes the formation process of inorganic functional slurry as an example to illustrate, and the components and contents are shown in Table 1, including the following steps:
[0086] S1, adding 4.5 parts by mass of silver-bismuth alloy to 2 parts by mass of alcohol benzoate and stirring evenly to obtain a first dispersed slurry;
[0087] S2, adding 1.5 parts by mass of acetylene alcohol-modified silicone into the first dispersed slurry and stirring evenly to obtain a second dispersed slurry, and stirring and dispersing the slurry with a dispersing paddle for 60-90 minutes;
[0088] S3. Evenly mix the treated second dispersed slurry with 64 parts by mass of an organic carrier and 28 parts by mass of ethanol to obtain an inorganic functional slurry.
[0089] Example 6
[0090] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0091] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 3 parts by mass of inorganic functional slurry obtained in Example 1 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0092] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 0.47 mΩ·cm 2 , line resistance is 2.40mΩ·cm 2 , the photoelectric conversion efficiency is 25.33%.
[0093] Example 7
[0094] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0095] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 4 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 4 parts by mass of inorganic functional slurry obtained in Example 1 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0096] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 0.45 mΩ·cm 2 , the line resistance is 2.42mΩ·cm 2 , the photoelectric conversion efficiency is 25.29%.
[0097] Example 8
[0098] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0099] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 3 parts by mass of inorganic functional slurry obtained in Example 2 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0100] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 0.43 mΩ·cm 2 , the line resistance is 2.59mΩ·cm 2 , the photoelectric conversion efficiency is 25.31%.
[0101] Example 9
[0102] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0103] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 4 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 4 parts by mass of inorganic functional slurry obtained in Example 2 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0104] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 0.45 mΩ·cm 2 , the line resistance is 2.51mΩ·cm 2 , the photoelectric conversion efficiency is 25.25%.
[0105] Example 10
[0106] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0107] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 3 parts by mass of inorganic functional slurry obtained in Example 3 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0108] According to Table 3, the line resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 2.33 mΩ·cm 2 , reducing the line resistance and the photoelectric conversion efficiency is 25.30%.
[0109] Combined Figure 2 and Figure 3 As shown, Figure 2 The results of the reaction between antimony trioxide and silicon are given, and it can be seen that the reaction between antimony trioxide and silicon generates the morphology of corrosion pits; Figure 3 The reaction between the front silver-aluminum paste with antimony trioxide and silicon is given. It can be seen that the front silver-aluminum paste containing antimony trioxide also generates corrosion pit morphology after reacting with silicon. This shows that when antimony trioxide is used in the front silver-aluminum paste, it can react with the silicon wafer surface during the sintering process, and can reduce the contact resistance and / or line resistance.
[0110] Embodiment 11
[0111] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0112] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 4 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 4 parts by mass of inorganic functional slurry obtained in Example 3 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0113] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 0.58 mΩ·cm 2 , the line resistance is 2.31mΩ·cm 2 , the photoelectric conversion efficiency is 25.31%.
[0114] Combined Figure 2 and Figure 3 As shown, Figure 2 The results of the reaction between antimony trioxide and silicon are given, and it can be seen that the reaction between antimony trioxide and silicon generates the morphology of corrosion pits; Figure 3 The reaction between the front silver-aluminum paste with antimony trioxide and silicon is given. It can be seen that the front silver-aluminum paste containing antimony trioxide also generates corrosion pit morphology after reacting with silicon. This shows that when antimony trioxide is used in the front silver-aluminum paste, it can react with the silicon wafer surface during the sintering process, and can reduce the contact resistance and / or line resistance.
[0115] Example 12
[0116] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0117] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 3 parts by mass of inorganic functional slurry obtained in Example 4 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0118] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 0.57 mΩ·cm 2 , the line resistance is 2.38mΩ·cm 2 , the photoelectric conversion efficiency is 25.31%.
[0119] Combined Figure 4As shown, the silver-aluminum paste containing aluminum-magnesium alloy on the front side reacts with silicon to generate corrosion pit morphology, which indicates that magnesium-aluminum alloy can react with the silicon wafer surface during the sintering process to reduce the contact resistance.
[0120] Embodiment 13
[0121] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0122] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 4 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 4 parts by mass of inorganic functional slurry obtained in Example 4 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0123] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 0.52 mΩ·cm 2 , the line resistance is 2.37mΩ·cm 2 , the photoelectric conversion efficiency is 25.31%.
[0124] Combined Figure 4 As shown, the silver-aluminum paste containing aluminum-magnesium alloy on the front side reacts with silicon to generate corrosion pit morphology, which indicates that magnesium-aluminum alloy can react with the silicon wafer surface during the sintering process to reduce the contact resistance.
[0125] Embodiment 14
[0126] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0127] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 3 parts by mass of inorganic functional slurry obtained in Example 5 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0128] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 0.38 mΩ·cm 2 , line resistance is 2.35mΩ·cm 2 , the photoelectric conversion efficiency is 25.38%.
[0129] Combined Figure 5As shown, the front silver-aluminum paste containing silver-bismuth alloy reacts with silicon to generate corrosion pit morphology, which indicates that the silver-bismuth alloy can react with the silicon wafer surface during the sintering process to reduce the contact resistance.
[0130] Embodiment 15
[0131] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0132] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 4 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 4 parts by mass of inorganic functional slurry obtained in Example 5 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0133] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this embodiment is 0.39 mΩ·cm 2 , the line resistance is 2.37mΩ·cm 2 , the photoelectric conversion efficiency is 25.33%.
[0134] Combined Figure 5 As shown, the front silver-aluminum paste containing silver-bismuth alloy reacts with silicon to generate corrosion pit morphology, which indicates that the silver-bismuth alloy can react with the silicon wafer surface during the sintering process to reduce the contact resistance.
[0135] Comparative Example 1
[0136] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0137] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 8 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, and 0.5 parts by mass of epoxy resin were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0138] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.62 mΩ·cm 2 , line resistance is 2.60mΩ·cm 2 , the photoelectric conversion efficiency is 25.28%.
[0139] Comparative Example 2
[0140] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0141] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 7.5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 0.5 parts by mass of inorganic functional slurry obtained in Example 1 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0142] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.59 mΩ·cm 2 , the line resistance is 2.57mΩ·cm 2 , the photoelectric conversion efficiency is 25.30%.
[0143] Comparative Example 3
[0144] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0145] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 3 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 5 parts by mass of inorganic functional slurry obtained in Example 1 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0146] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.50 mΩ·cm 2 , the line resistance is 2.47mΩ·cm 2 , the photoelectric conversion efficiency is 25.31%.
[0147] Comparative Example 4
[0148] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0149] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 7.5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 0.5 parts by mass of inorganic functional slurry obtained in Example 2 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0150] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.60 mΩ·cm 2 , the line resistance is 2.58mΩ·cm 2, the photoelectric conversion efficiency is 25.28%.
[0151] Comparative Example 5
[0152] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0153] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 3 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 5 parts by mass of inorganic functional slurry obtained in Example 2 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0154] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.50 mΩ·cm 2 , line resistance is 2.60mΩ·cm 2 , the photoelectric conversion efficiency is 25.29%.
[0155] Comparative Example 6
[0156] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0157] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 7.5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 0.5 parts by mass of inorganic functional slurry obtained in Example 3 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0158] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.62 mΩ·cm 2 , the line resistance is 2.54mΩ·cm 2 , the photoelectric conversion efficiency is 25.28%.
[0159] Comparative Example 7
[0160] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0161] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 3 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 5 parts by mass of inorganic functional slurry obtained in Example 3 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0162] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.62 mΩ·cm 2 , the line resistance is 2.48mΩ·cm 2 , the photoelectric conversion efficiency is 25.29%.
[0163] Comparative Example 8
[0164] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0165] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 7.5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 0.5 parts by mass of inorganic functional slurry obtained in Example 4 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0166] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.61 mΩ·cm 2 , the line resistance is 2.51mΩ·cm 2 , the photoelectric conversion efficiency is 25.29%.
[0167] Comparative Example 9
[0168] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0169] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 3 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 5 parts by mass of inorganic functional slurry obtained in Example 4 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0170] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.59 mΩ·cm 2 , line resistance is 2.45mΩ·cm 2 , the photoelectric conversion efficiency is 25.33%.
[0171] Comparative Example 10
[0172] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0173] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 7.5 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 0.5 parts by mass of inorganic functional slurry obtained in Example 5 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0174] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.57 mΩ·cm 2 , the line resistance is 2.49mΩ·cm 2 , the photoelectric conversion efficiency is 25.35%.
[0175] Comparative Example 11
[0176] This example takes the preparation process of the front silver aluminum paste as an example to illustrate, and the components and contents are shown in Table 2, including the following steps:
[0177] 85.5 parts by mass of conductive silver powder, 1.5 parts by mass of aluminum powder, 3.5 parts by mass of glass powder, 3 parts by mass of organic carrier, 1 part by mass of fatty acid glyceride, 0.5 parts by mass of epoxy resin and 5 parts by mass of inorganic functional slurry obtained in Example 5 were mixed evenly and ground to a slurry fineness of ≤10 μm to obtain a front silver-aluminum slurry for an N-type TOPCon solar cell.
[0178] According to Table 3, the contact resistance of the cell formed by the silver-aluminum paste on the front side of this comparative example is 0.41 mΩ·cm 2 , line resistance is 2.40mΩ·cm 2 , the photoelectric conversion efficiency is 25.35%.
[0179] In summary, according to the results of Examples 6-15 and Comparative Example 1, it can be seen that when the inorganic functional paste is introduced into the front silver-aluminum paste, it helps to reduce the contact resistance and / or line resistance of the battery and improve the photoelectric conversion efficiency to a certain extent; secondly, according to the results of Examples 6-15 and Comparative Examples 2-11, when the content of the inorganic functional paste is 1 to 4 parts by mass, the contact resistance and / or line resistance of the corresponding battery is the lowest, and the photoelectric conversion efficiency is relatively high; when the content of the inorganic functional paste is lower than 1 part by mass or higher than 4 parts by mass, the contact resistance and / or line resistance of the corresponding battery are increased, and the photoelectric conversion efficiency is also decreased to varying degrees.
[0180] Table 1 Formulas of different inorganic functional slurries in Examples 1-5
[0181]
[0182] Table 2 Different front silver aluminum paste formulas in Examples 6-15 and Comparative Examples 1-11
[0183]
[0184]
[0185] Table 3 Electrical performance test results of front silver aluminum paste of Examples 6-15 and Comparative Examples 1-11
[0186]
[0187]
[0188] The present invention provides an inorganic functional slurry, a front silver-aluminum slurry for an N-type TOPCon solar cell and a preparation method thereof, which has the following beneficial effects: by introducing an inorganic functional additive into the front silver-aluminum slurry, the silver powder can be sintered, and at the same time react with silicon, so that the line resistance and / or contact resistance of the cell sheet is reduced. In addition, the preparation method of the present invention is simple, and the mixing effect of the slurry can be improved, and the dispersibility can be increased.
[0189] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A front silver-aluminum paste for an N-type TOPCon solar cell, characterized in that: include: 75-87 parts by mass of conductive silver powder; 1 to 5 parts by mass of aluminum powder; 3 to 15 parts by weight of an organic carrier; 2 to 6 parts by mass of glass powder; 1 to 3.5 parts by weight of an auxiliary agent; 1 to 4 parts by mass of an inorganic functional slurry, wherein: The inorganic functional slurry comprises: 55 to 85 parts by weight of an organic carrier; 2 to 20 parts by weight of an inorganic functional additive, wherein the inorganic functional additive comprises at least one of zinc oxide, titanium oxide, antimony trioxide, aluminum-magnesium alloy, and silver-bismuth alloy; 2 to 10 parts by mass of a dispersant; the dispersant comprises a first dispersing component and a second dispersing component; wherein the first dispersing component is alcohol benzoate; and the second dispersing component is acetylenic alcohol-modified silicone; 10 to 30 parts by mass of a solvent; The inorganic functional slurry is formed by the following method, including: adding the inorganic functional additive to the first dispersed component and stirring evenly to obtain a first dispersed slurry; Adding the second dispersed component into the first dispersed slurry and stirring evenly to obtain a second dispersed slurry, and performing a stirring and dispersing treatment; The treated second dispersed slurry is uniformly mixed with an organic carrier and a solvent to obtain an inorganic functional slurry.
2. The front silver-aluminum paste for N-type TOPCon solar cells according to claim 1, characterized in that: The D50 particle size of the inorganic functional additive is 0.08um to 1.6um.
3. The front silver-aluminum paste for N-type TOPCon solar cells according to claim 1, characterized in that: The content of the first dispersed component is 1 to 5 parts by mass, and the content of the second dispersed component is 1 to 5 parts by mass.
4. The front silver-aluminum paste for N-type TOPCon solar cells according to claim 1, characterized in that: The organic carrier includes 3 to 15 parts by mass of acrylic resin.
5. A method for preparing the front silver-aluminum paste of the N-type TOPCon solar cell according to any one of claims 1 to 4, the method comprising: forming an inorganic functional slurry; Conductive silver powder, aluminum powder, glass powder, organic carrier, additive and the inorganic functional slurry are uniformly mixed and ground to obtain the front silver-aluminum slurry of the N-type TOPCon solar cell.
Citation Information
Patent Citations
Silver-aluminum paste for front electrode of high-sheet-resistance N-type solar cell and preparation method of silver-aluminum paste
CN113764119A
TOPCon front silver-aluminum paste containing aluminum-based alloy and preparation method of TOPCon front silver-aluminum paste
CN115497660A
